2005
DOI: 10.1186/1471-2105-6-170
|View full text |Cite
|
Sign up to set email alerts
|

SeqX: a tool to detect, analyze and visualize residue co-locations in protein and nucleic acid structures

Abstract: BackgroundThe interacting residues of protein and nucleic acid sequences are close to each other – they are co-located. Structure databases (like Protein Data Bank, PDB and Nucleic Acid Data Bank, NDB) contain all information about these co-locations; however it is not an easy task to penetrate this complex information. We developed a JAVA tool, called SeqX for this purpose.ResultsSeqX tool is useful to detect, analyze and visualize residue co-locations in protein and nucleic acid structures. The usera. select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A JAVA tool called SeqForm, developed by us, was used to select sequence residues in predefined phases (every third in our case) and for residue replacements [12]. Amino acid collocations were detected and evaluated by another tool, SeqX [13].…”
Section: Methodsmentioning
confidence: 99%
“…A JAVA tool called SeqForm, developed by us, was used to select sequence residues in predefined phases (every third in our case) and for residue replacements [12]. Amino acid collocations were detected and evaluated by another tool, SeqX [13].…”
Section: Methodsmentioning
confidence: 99%
“…Con-Struct Map ( 16 ), CMWeb ( 17 ) and CMA ( http://ligin.weizmann.ac.il/cma/ ) allows structural comparison of proteins by analysing the contact maps, and CMA also supports analysis of protein complexes. Standalone programs such as SeqX ( 18 ), Protmap2D ( 19 ) and CMview ( 20 ) allow construction and basic analysis of contact maps. RING provides several methods for the construction of residue interaction network, which can be analysed using Cytoscape ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…However new bioinformatics tools [39] and a large protein structure database (PDB) became available. Statistical analyzes of amino-acid colocations in real protein structures revealed that the redundant Genetic Code contains even information necessary to protein folding and interactions [40,41].…”
Section: Discussionmentioning
confidence: 99%